DECISION SUPPORT SYSTEM TO DETERMINE THE LEVEL OF ADDICTION TO MOBILE LEGENDS ONLINE GAMES USING THE NAÏVE BAYES METHODE - S, Amri Yuda; Hasugian, Abdul Halim (UIN Sumatera Utara, 2023)
Addiction is liking and possessing something so much that you forget about other things. Gaming addiction is a type of addiction caused by internet technology. Game addiction itself is caused by several factors including Dominion, Timeless, Mood Swing, Healtium, Insocial and, Maladiptive Daydreaming. The purpose of this study is to accurately calculate and classify the level of online game addiction of FST UINSU students. The type of method used is a systematic quantitative analysis method of Naive Bayes Algorithm. After completing the calculation procedure, the search results show that the value obtained is very high at 91.67%. Healtium and Dominum factors are the highest causes of addiction because obviously these two factors have very high weight values